DIGITALIZING LEADERSHIP OPTIMALISASI GOOGLE SITE UNTUK KEGIATAN ORGANISASI SISWA DI SMKN 7 KOTA SERANG - Istiqomah Rohmawati; Joko Yuwono; Pramadjaya, Angga; Muhamad Azis Rachmaditya; Lutfi Yulianto (LPPM Universitas Pamulang, 2024)
ABSTRACT Digital leadership involves using technology to increase effectiveness and efficiency in managing teams and organizations. This covers various aspects, such as digital communication, data-based decision making, and the use of online collaboration tools. By analyzing the problems that exist at SMKN 7 Serang City, namely the lack of technological knowledge among employees, limitations in collaboration and communication, the difficulty of accessing information on activities in school. So this PkM group held training related to Digitalizing Leadership, Optimizing Google Sites for student organization activities. The result of implementing this PkM activity is that the implementation of Google Site in student organization activities has increased efficiency in conveying information and transparency in organizational management. Every student or teacher can easily access the latest information and see developments in the organization's work program. Of the respondents who had filled out the online questionnaire provided, for the point of ease of use of the Google site, 45% answered agree, and 55% answered strongly agree. For information points needed on the Google site, 35% answered agree and 65% answered strongly agree. For the point that the Google site makes the process of disseminating information easier, 40% answered agree, 60% answered strongly agree. For the point of making it easier to collaborate with the Google site, 20% answered agree and 80% answered strongly agree. For the satisfaction point of using the Google site, 32% answered agree and 68% answered strongly agree. Digitalizing Leadership, Optimization, Google Site, Organization.